Monitoring the Future: A Continuing Study of American Youth (8th- and 10th-Grade Surveys), 2004 - Johnston, Lloyd D. ([Verlag nicht ermittelbar], 2005)
These surveys of 8th- and 10th-grade students are part of a series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth. Students in each grade are randomly assigned to complete one of four questionnaires, each with a different subset of topical questions but containing a set of "core" questions on demographics and drug use. There are more than 450 variables across the questionnaires. Drugs covered by this survey include amphetamines (stimulants), barbiturates (tranquilizers), other prescription drugs, tobacco, alcohol, inhalants, steroids, marijuana, hashish, LSD, hallucinogens, cocaine, crack, ecstasy, methamphetamine, and injection drugs such as heroin.